Invulnerability in innovation networks: the importance of technology cluster coupling and network centralization. Issue 4 (3rd April 2023) - Li, Li; Lin, Haifen; Lyu, Yibo; Cheng, Lu
ABSTRACT: The high fragility and failure rate of technological innovation networks prevent firms and industries from successfully developing innovation capacity and competitiveness. This study offers a network perspective on how technology cluster coupling reinforces innovation network invulnerability. By using 142 patent citation networks from the renewable energy industry, we conduct patent citation network and regression analyses of a mediating model. The results show that network centralisation plays a partly negative mediating role in the positive relationship between technology cluster coupling and innovation network invulnerability. This study enriches the antecedent study of innovation network invulnerability by expanding interactions from the individual-level to the community-level and contributes to the internal mechanisms of technology cluster coupling and network invulnerability by emphasising the critical role of network centralisation. Our findings offer implications for policy makers who seek to govern technology clusters aimed at strengthening the steady development of innovation networks.